Nutrient dynamics and coupling with biological processes and physical conditions in the Bohai Sea - Liang, Wen; Wang, Yun; Liu, Sumei; Wang, Mengxue; Zhao, Liang; Liu, Chongcong; Zhang, Xiaotong; Wu, Nian; Wang, Lingyan; Zhu, Dongdong; Ma, Yuwei; Luo, Chang (Frontiers in Marine Science, 2022)
The Bohai Sea is a habitat for economically important fish in China, but its ecological environment has changed significantly, and it is necessary to further clarify the dynamics and the internal resupply channels of nutrients in the Bohai Sea. Based on four field observations in the Bohai Sea from May to December 2019, the nutrient dynamics were addressed. The concentration of dissolved inorganic nutrients was depleted throughout the water column in spring and in the euphotic zone in summer and accumulated in the bottom water in summer and in the water column in autumn and winter. Relative phosphorus limitation was present in Laizhou Bay and its surrounding area in all seasons, while relative silicon limitation was evident in spring and relative nitrogen limitation was significant in summer in most other study aeras. The results of end-member mixing model illustrated significant seasonal differences in the nutrient uptake ratios, which may be related to various factors such as different phytoplankton composition and phosphorus turnover rates. Turbulent entrainment was an important nutrient pathway for primary production in the euphotic zone of Central Bohai Sea during the stratification season, with an estimated average nutrient flux of 6.04 ± 9.63, 0.22 ± 0.19 and 6.97 ± 6.61 mmol·m-2·d-1 for DIN, DIP and DSi, respectively.